Correlation between thermal deformation and microcracking in concrete during cryogenic cooling. (January 2016) - Kogbara, Reginald B.; Iyengar, Srinath R.; Grasley, Zachary C.; Rahman, Syeda; Masad, Eyad A.; Zollinger, Dan G.
Abstract: Thermal deformation behavior of concrete mixtures from limestone and trap rock aggregates has been related to microcracking during cryogenic cooling. The study was aimed at comparing the suitability of the concretes for direct containment of liquefied natural gas (LNG). The results showed strong correlation between the thermal strain rate and the acoustic emission (AE) cumulative hits rate in the concretes. The closeness of the average thermal expansion coefficient of the trap rock mixture over the ambient to cryogenic temperature range to that of 9% Ni or carbon-steel, and its lower cumulative energy emission corroborates previous observations on its porosity, permeability and microstructural behavior. These likely make it more suitable for direct LNG containment. Highlights: Thermal strains are related to microcracking during cryogenic cooling of concretes. Strong correlation existed between thermal strain rate and AE cumulative hits rate. The average CTE of the trap rock concrete mixture was close to that of 9% Ni steel. Suitability of trap rock aggregate concrete for direct LNG containment is shown.